Encouraging morecreativity in organizations: the importance of employees’ intrinsic motivation andworkengagement - Aldabbas, Hazem (2022)
Purpose– Thispaper aims to investigate the contribution of perceived organizational support (POS), work engagement(WE)andintrinsic motivation(IM) on employee creativity (EC). Design/methodology/approach– This study conducted a questionnaire survey obtaining 370 respondents employed in the United Arab Emirates in 6 organizations operating in services industries. The authors test their hypothetical model based on regression analysis. Findings– The main findings are that WE mediates the relationship between POS and EC. Further, the effect of POS on EC is moderated by IM. The results also indicated that the indirect effect of POS on EC through WEwasmoderatedbyIM.ThepatheffectisstrongerforemployeeswithhighIM. Originality/value– This study sheds light on the effect of POS on EC through WE and IM in the workplace, making a significant contribution to the POS and EC literatures by offering insights on when and howIMandWEenhancesEC. Keywords Perceived organizational support, Work engagement, Intrinsic motivation, Employee creativity, Social exchange theory PapertypeResearch paper